Multifactorial relationship involved in growth processes facial growth. "Focused on the language of Alexandre Petrovic's Servosystem": Literature review. - Cruz Gallegos, Víctor Alexander (2022)
The knowledge of being able to determine skeletal maturation and missing growth potential is an essential element when planning orthodontic treatment. The study of craniofacial growth and development is a complex and essential process for the diagnosis and resolution of malocclusions. Craniofacial growth and development occurs by the process of growth and ossification of the hyaline cartilage, thus promoting the theory of the servosystem, which is a system with feedback, of constant renewal, which generates a new response. From this point of view, Petrovic considers involving orthopedic appliances, where he explained that the mandibular condyle can respond to mechanical stimuli causing stress at the level of anatomical structures due to orthodontic forces through the interaction of blood circulation and cells white cells that as a result form bone remodeling, which could be inhibitory or synergistic. The objective of this review is to summarize recent concepts on craniofacial growth, focused on the theory of Alexandre Petrovic and his collaborators, with the development of general scientific knowledge and inspire the creation of a new, more integrated multidisciplinary approach based on the person, through bases of MEDLINE, EMBASE, Pubmed, and Google Scholar data, which were evaluated, and synthesized, to be part of the next literature review.